The Influence of “CILUKBA” Comic Education on Knowledge of Parenting Patterns in Preschool Age Children at Kindergarten Aisiyah Bustanul Athfal 2 Karang Tengah Purbalingga - Arinta Lyra Anggraeni; Wahyu Riyaningrum; Sodikin Sodikin; Yuliarti Yuliarti (UM Purwokerto Press, 2024)
Background:Parenting style is the attitude and way parents relate to their children. Preschool children are children aged between 3-6 years. Positive parenting is parenting that is based on affection, respect, protection of rights, stimulation of growth and development, and a warm attitude. The importance of providing education on positive parenting knowledge can be done with comics as a medium for delivering educational material. Method: Quasi-experimental research method with an experimental research design of one group pretest-posttest design. The sample was a total sampling of 36 respondents according to the inclusion criteria using a questionnaire instrument. Results:The research results showed that there was a difference in the average value of knowledge before and after education, namely 12.25 (fair) to 18.19 (good) with a p-value (0.000). Conclusion:The comic media